Oral exfoliative cytology for the non-invasive diagnosis in X-linked Emery–Dreifuss muscular dystrophy patients and carriers - Sabatelli, P; Squarzoni, S; Petrini, S; Capanni, C; Ognibene, A; Cartegni, L; Cobianchi, F; Merlini, L; Toniolo, D; Maraldi, N.M (Neuromuscular disorders : NMD, 1998)
Emery–Dreifuss muscular dystrophy (EMD) is an inherited myopathy characterised by muscle contractures, progressive muscle wasting and weakness, with humeroperoneal distribution. Cardiac arrhythmia and heart conduction block are also important characteristics of this disease. The X-linked form of EMD is caused by the absence of emerin, encoded by the STA gene (Xq28). Emerin is normally localised in muscle and other tissues at the nuclear rim. Currently, muscle and skin biopsies are used for the immunohistochemical diagnosis. We demonstrate that emerin is present in the cheek oral mucosa, in the exfoliating epithelial cells, and we propose the collection of these cells as a new method for the diagnosis of X-linked EMD patients and the detection of carriers by immunofluorescence techniques: smears from healthy subjects contained about 98% emerin-positive cells, those from X-linked EMD patients contained none and those from carriers contained about 45%. The technique is completely non-invasive, simple, repeatable and inexpensive.